The effects of sport dance on brain connectivity and body intelligence. Issue 5 (3rd July 2016) - Kim, Young Jae; Cha, Eun Joo; Kang, Kyoung Doo; Kim, Bung-Nyun; Han, Doug Hyun
ABSTRACT: Dancing is characterised by physical movement in accordance with rhythm perception. Twelve sport dancers and 12 age- and sex-matched young adults who had no dance experience (control group) were recruited. Body intelligence and brain activity were assessed in both groups using the Body Intelligence Scale (BIS) and resting state functional magnetic resonance imaging. BIS scores of dancers were higher than those of control subjects. The dancer group showed increased functional connectivity from the precentral gyrus to the right cingulate gyrus, right occipital fusiform gyrus, right inferior frontal gyrus, right medial frontal gyrus, left inferior frontal gyrus, right parietal postcentral gyrus, and right frontal lobe compared with control subjects. Sport dancers had increased body intelligence sensitivity compared with matched controls. In addition, the characteristics of dance, including physical movement in accordance with rhythm perception, might be associated with increased brain activity in the somatosensory and rhythm perception networks.